Gatekeepers Gone Wrong: Reforming the Chapter 9 Eligibility Rules - Laura N. Coordes (Washington University Law Review, 2017)
In order to gain access to chapter 9 bankruptcy, municipalities must demonstrate that they meet several eligibility requirements. These requirements were put in place to prevent municipalities from making rash decisions about filing for bankruptcy. Too often, however, these requirements impede municipalities from attaining desperately needed relief. This Article demonstrates that as currently utilized, the chapter 9 eligibility rules overemphasize deterrence and are not rationally connected to the reasons the chapter 9 bankruptcy system was developed. This Article therefore posits that the chapter 9 eligibility requirements should be relaxed. To support this claim, the Article conducts a detailed analysis of the history and theory of chapter 9 to determine the primary reasons for the eligibility rules and the core functions of a municipal bankruptcy solution. It then demonstrates how many of the concerns driving the eligibility rules’ existence are addressed in other chapter 9 mechanisms and proposes sweeping revisions to the eligibility rules to facilitate appropriate access to chapter 9. Specifically, municipalities in fiscal distress should be able to access bankruptcy when they demonstrate a need for the primary types of assistance that bankruptcy can best provide: nonconsensual debt adjustment, elimination of the holdout creditor problem, and breathing space. Through its analysis, this Article brings needed attention to the broader questions of who should have access to bankruptcy and when that access should be granted.
Keywords: chapter 9 bankruptcy; chapter 9 eligibility requirements; municipality bankruptcy; bankruptcy law; Bankruptcy Code